Evaluation of Different Transition Periods in Feeding Live Feed for Tiger Shovelnose Catfish (Pseudoplatystoma punctifer, Castelnau 1855) Larvae - Demas Agatri; Achmad Noerkhaerin Putra; Mustahal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The production of tiger shovelnose catfish (TSN) is limited by the very low growth during feeding transition in phase larvae. This research aims to evaluate the difference in feed transition period from nauplii Artemia sp. to Tubifex sp. on the growth and activity of digestive enzymes of TSN larvae. TSN larvae 1 dph (day post hatching) with total length of 4.05±0.16 mm and weight of 4.18±0.67 mg were used in this study. Nine aquariums with 10 L of water were stocked with larvae at a density 30 larvae/L. This study consisted of three treatments of different feed transition time in triplicates i.e. transition at 9 dph (P1), 10 dph (P2) and 11 dph (P3). The result showed that the transitional on 11 dph (P3) recorded the highest total length (36.9±0.56 mm), total weight (242.5±2.4 mg), daily length growth rate (13.43±0.81 %.mm/day), daily weight growth rate (25.4±0.06 %.mg/day), survival rate (81.7±3.1%), and protease enzyme activity (0.222±0.019 IU/mL) compared to 10 dph (P2) and 9 dph (P1). The transition period of 11 days is the mostappropriate time to change the feed for nauplii Artemia sp. to Tubifex sp. in TSN larvae because it produces the best growth and digestive enzyme activity values.